Perioperative increase in neutrophil CD64 expression is an indicator for intra-abdominal infection after colorectal cancer surgery - Kerin-Povšič, Milena (Radiology and oncology (Ljubljana), 2017)
Colorectal surgery is associated with a high incidence of postoperative infections. Early clinical signs are difficult to distinguish from the systemic inflammatory response related to surgical trauma. Timely diagnosis may significantly improve the outcome. The objective of this study was to compare a new biomarker index CD64 for neutrophils (iCD64n) with standard biomarkers, white blood cell (WBC) count, neutrophil/lymphocyte ratio (NLR), C-reactive protein (CRP) and procalcitonin (PCT) for the early detection of postoperative infection. Methods. The prospective study included 200 consecutive patients with elective colorectal cancer surgery. Postoperative values of biomarkers from the postoperative day (POD) 1 to POD5 were analysed by the receiver operating characteristic (ROC) analysis to predict infection. The Cox regression model and the Kaplan-Meier method were used to assess prognostic factors and survival. Results. The increase of index CD64n (iCD64n) after surgery, expressed as the ratio iCD64n after/before surgery was a better predictor of infection than its absolute value. The best 30-day predictors of all infections were CRP on POD4 (AUC 0.72, 99% CI 0.61%0.83) and NLR on POD5 (AUC 0.69, 99% CI 0.57%0.80). The best 15-day predictors of organ/ space surgical site infection (SSI) were the ratio iCD64n on POD1 (AUC 0.72, 99% CI 0.58%0.86), POD3 (AUC 0.73, 99% CI 0.59%0.87) and CRP on POD3 (AUC 0.72, 99% CI 0.57%0.86), POD4 (AUC 0.79, 99% CI 0.64%0.93). In a multivariate analysis independent risk factors for infections were duration of surgery and perioperative transfusion while the infection itself was identified as a risk factor for a worse long-term survival. Conclusions. The ratio iCD64n on POD1 is the best early predictor of intra-abdominal infection after colorectal cancer surgery. CRP predicts the infection with the same predictive value on POD3.
Keywords: CD64; colorectal surgery; index CD64n; kolorektalna kirurgija; pooperativne okužbe; postoperative infection